A novel multiplex qPCR assay for clinical diagnosis of non-human malaria parasites-Plasmodium knowlesi and Plasmodium cynomolgi - Das, Ram; Vashisht, Kapil; Pandey, Kailash C. (Frontiers in Veterinary Science, 2023)
The imminent risk of zoonoses of non-human malaria parasites is not far from reality in India, as has been observed in the case of Plasmodium knowlesi (Pk), and so is possible with P. cynomolgi (Pc), already reported from South East Asian countries. Therefore, a novel multiplex qPCR assay was developed and evaluated for detection of non-human malaria parasites- Pk and Pc in populations at risk. The qPCR assay successfully amplified the target 18S rRNA gene segment from Pk and Pc and was highly specific for Pk and Pc parasites only, as no cross reactivity was observed with P. falciparum (Pf), P. vivax (Pv), P. malariae (Pm) and P. ovale (Po). Standard curves were generated to estimate the limit of detection (LOD) of Pk and Pc parasites DNA (0.00275 & 0.075 ng/µl, respectively). Further, the qPCR assay was evaluated in 250 symptomatic and asymptomatic suspected human blood samples from malaria endemic areas of North Eastern states of India. Due to COVID-19 pandemic situation during 2020-21, the sample accessibility was difficult, however, we managed to collect 250 samples. The samples were tested for Pf and Pv using conventional PCR- 14 Pf and 11 Pv infections were observed, but no Pk and Pc infections were detected. For Pk infections, previously reported conventional PCR was also performed, but no Pk infection was detected. The multiplex qPCR assay was observed to be robust, quick, cost-effective and highly sensitive as compared to the currently available conventional PCR methods. Further validation of the multiplex qPCR assay in field setting is desirable, especially from the high-risk populations. We anticipate that the multiplex qPCR assay would prove to be a useful tool in mass screening and surveillance programs for detection of non-human malaria parasites towards the control and elimination of malaria from India by 2030.